A point ( x , y ) in the first quadrant is 6 0 0 units closer to the point ( 5 0 0 , 0 ) than to the point ( − 5 0 0 , 0 ) and is a distance of 4 0 0 units away from the origin. The value of x is 2 A . Find A .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Suppose M is the ( x , y ) point, B is the ( − 5 0 0 , 0 ) point, C is the ( 5 0 0 , 0 ) point and O is the origin ( 0 , 0 ) . Add the points. Draw a perpendicular M E from M over B C . We have to find O E .
M B − M C = 6 0 0 ,
O M = 4 0 0 ,
B O = O C = 5 0 0
In Obtuse triangle ∆MOB , M B 2 = M O 2 + B O 2 + 2 B O . O E _ _ _ (1)
In Acute triangle ∆MOC , M C 2 = M O 2 + O C 2 − 2 O C . O E _ _ _ (2)
Substract (2) from (1)
M B 2 − M C 2 = B O 2 − O C 2 + 2 B O . O E + 2 O C . O E
( M B + M C ) ( M B − M C ) = 4 B O . O E [As BO=CO]
( M B + M C ) × 6 0 0 = 4 × 5 0 0 × O E
O E = 2 0 0 0 6 0 0 × ( M B + M C ) _ _ _ (3)
.
From M B − M C = 6 0 0
M B 2 = M C 2 + 1 2 0 0 M C + 6 0 0 2
.
M B 2 + M C 2 = 2 ( M O 2 + B O 2 ) [Apollonius theorem]
M C 2 + 1 2 0 0 M C + 6 0 0 2 + M C 2 = 2 × ( 4 0 0 2 + 5 0 0 2 )
2 M C 2 + 1 2 0 0 M C − 4 6 0 0 0 0 = 0
M C 2 + 6 0 0 M C − 2 3 0 0 0 0 = 0
.
Now using the formula x = 2 a − b ± b 2 − 4 a c
M C = 4 0 0 × 2 − 3 0 0
Similarly, M B = 4 0 0 2 + 3 0 0
M B + M C = 8 0 0 2
.
Put the value in (3)
O E = 2 0 0 0 6 0 0 × 8 0 0 2
O E = x = 2 4 0 2
So A = 2 4 0
We have : ( x − 5 0 0 ) 2 + y 2 = s q r t ( x + 5 0 0 ) 2 + y 2 − 6 0 0 and x 2 + y 2 = 4 0 0 . So, now we are just need to solve the following equation to get x.
Squaring both equations, we have : x 2 + y 2 = 1 6 0 0 0 0 and x 2 − 1 0 0 0 x + 2 5 0 0 0 0 + y 2 = x 2 + 1 0 0 0 x + 2 5 0 0 0 0 + y 2 − 1 2 0 0 x 2 + 1 0 0 0 x + 2 5 0 0 0 0 + y 2 + 3 6 0 0 0 0 ,
which give 1 2 0 0 4 1 0 0 0 0 + 1 0 0 0 x = 2 0 0 0 x + 3 6 0 0 0 0 , 3 4 1 0 0 0 0 + 1 0 0 0 x = 5 x + 9 0 0
Squaring again : 3 6 9 0 0 0 0 + 9 0 0 0 x = 2 5 x 2 + 9 0 0 0 x + 8 1 0 0 0 0 2 5 x 2 = 2 8 8 0 0 0 0 x = 2 4 0 2 So, we get A = 2 4 0
From the difference in distances we get,
sqrt( ((x+500)^2) + (y^2) )) - sqrt( ((x-500)^2) + (y^2) ) = 600 (1)
From distance from origin we get,
sqrt( (x^2) + (y^2) ) = 400 (2)
Squaring (2), we get
(x^2) + (y^2) = 160000
Simplifying (1), we get
sqrt( (x^2) + (y^2) ) + 250000 + 1000x ) - sqrt( (x^2) + (y^2) + 250000 - 1000x ) = 600
Replacing (x^2) + (y^2) = 160000 and squaring gets,
410000 + 1000x + 410000 - 1000x - 2*( sqrt( (410000^2) - 1000000(x^2) ) ) = 360000
This gives, 230000 = sqrt( (410000^2) - 1000000(x^2) )
Squaring on both sides gets, (410000^2) - (230000^2) = 1000000(x^2)
(x^2) = 1152/100
Or x = 240*sqrt(2)
Thus A = 240
In Analytic Geometry, the distance between two points a & b can be calculated using the following formula :
ab = \sqrt{(x 2-x 1)^2 + (y 2-y 1)^2} ,where a(x 1, y 1), b(x 2, y 2)
So, using this and the problem information, the following is true :
\sqrt{(x-500)^2 + y^2} + 600 = \sqrt{(x-(-500))^2 + y^2} \sqrt{x^2 - 1000x + 250000 + y^2} + 600 = \sqrt{x^2 + 1000x + 250000 + y^2} \rightarrow 1 \sqrt{x^2 + y^2} = 400 Then x^2 + y^2 = 160000 y^2 = 160000 - x^2 \rightarrow 2
By using y^2 from the second equation in the first equation, Then
\sqrt{x^2-1000x+250000+160000-x^2}+600 = \sqrt{x^2+1000x+250000+160000-x^2} then \sqrt{410000+1000x}-\sqrt{410000-1000x} = 600 \sqrt{4100+10x}-\sqrt{4100-10x} = 60 4100+10x+4100-10x-2 \sqrt{4100+10x} \sqrt{4100-10x} = 60 4100-\sqrt{4100+10x} \sqrt{4100-10x} = 1800 \sqrt{16810000-100x^2} = 2300 16810000-100x^2 = 5290000 x^2 = 168100-52900 = 115200 x = \sqrt{2} 240 = \sqrt{2}*A Then A = 240
From the second condition, we get that x 2 + y 2 = 4 0 0 or x 2 + y 2 = 1 6 0 0 0 0
From the first condition, we get that ( x − 5 0 0 ) 2 + y 2 − ( x + 5 0 0 ) 2 + y 2 = 6 0 0 x 2 − 1 0 0 0 x + 2 5 0 0 0 0 + y 2 − x 2 + 1 0 0 0 x + 2 5 0 0 0 0 + y 2 = 6 0 0 substituting the first equation we found in, − 1 0 0 0 x + 2 5 0 0 0 0 + 1 6 0 0 0 0 − 1 0 0 0 x + 2 5 0 0 0 0 + 1 6 0 0 0 0 = 6 0 0 − 1 0 0 0 x + 4 1 0 0 0 0 − 1 0 0 0 x + 4 1 0 0 0 0 = 6 0 0 squaring both sides gives, − 1 0 0 0 x + 4 1 0 0 0 0 + 1 0 0 0 x + 4 1 0 0 0 0 − 2 1 6 8 1 0 0 0 0 0 0 0 0 − 1 0 0 0 0 0 0 x 2 = 3 6 0 0 0 0 (820000-2\sqrt{168100000000-1000000x^2}=360000) − 2 1 6 8 1 0 0 0 0 0 0 0 0 − 1 0 0 0 0 0 0 x 2 = − 4 6 0 0 0 0 1 6 8 1 0 0 0 0 0 0 0 0 − 1 0 0 0 0 0 0 x 2 = 2 3 0 0 0 0 squaring again gives, 1 6 8 1 0 0 0 0 0 0 0 0 − 1 0 0 0 0 0 0 x 2 = 5 2 9 0 0 0 0 0 0 0 0 1 0 0 0 0 0 0 x 2 = 1 1 5 2 0 0 0 0 0 0 0 0 x 2 = 1 1 5 2 0 0 so x = 2 4 0 s q r t 2 and the A = 2 4 0
Distance from origin to (x,y) is 400 so x^2+y^2=(400)^2 the question, mathematically, states that root((x+500)^2+y^2) + 600 = root((x-500)^2+y^2) =>root(400^2+500^2+1000x) + 600 = root(400^2+500^2-1000x) now, putting k^2=400^2+500^2 we get root(k^2+1000x) - root(k^2-1000x) = -600 squaring, 2k^2-2root(k^4-10^6x^2)=600^2 putting k^2 value and x^2=2A^2, 2A^2.10^6=(41^2-23^2).10^8 =>A=8.3.10=240
Since (x,y) is in first quadrant and is 600 units closer to (500,0) than (-500,0), then by using distance formula: ( x + 5 0 0 ) 2 + y 2 = ( x − 5 0 0 ) 2 + y 2 + 6 0 0 and (x,y) is 400 from origin, hence: x 2 + y 2 = 4 0 0 and x 2 + y 2 = 4 0 0 2 after substituting y 2 = 4 0 0 2 − x 2 into the first equation and further calculation for x 2 , we'll get x 2 = 1 1 5 2 0 0 and x = 2 4 0 2 .Hence, A = 2 4 0
lets start with "a point (x,y) is a distance of 400 units away from the origin."
using distance between two points formula : \sqrt { (y2-y1)^2 + (x2-x1)^2 }
we get : \sqrt{(x-0)^2 + (y-0)^2)} = 400 removing sqrt we get x^2 + y^2 = 160000
so y^2 = 160000 - x^2 \rightarrow equ 1
assuming distance between point (x,y) and point (-500,0) is "z" using same formula:
z= \sqrt{(x+500)^2 + (y-0)^2} z^2= x^2 +1000x +250000 +y^2
eliminating y^2 by substituting from equ 1
we get :
z^2= 410000 +1000x \rightarrow equ 2
as " point (x,y) is 600 units closer to the point (500,0) than to the point (−500,0)" and if distance between point (x,y) and point (-500,0) is "z" then distance between point (x,y) and (500,0) must be 600 unit smaller . so distance between point(x,y) and point (500,0) equals "z-600" .
using same formula:
z-600 = \sqrt{(x-500)^2 + (y-0)^2} removing sqrt we get: (z-600)^2=(x-500)^2+y^2
z^2-1200z+360000=x^2-1000x+250000+y^2 z^2-1200z=x^2-1000x+y^2 - 110000 eliminating y^2 by substituting from equ 1
we get:
z^2-1200z=50000-1000x \rightarrow equ 3
by substituting with equ 2 in equ 3 z^2= 410000 +1000x \rightarrow equ 2 z=\sqr{410000 +1000x}
z^2-1200z=50000-1000x \rightarrow equ 3
we get:
410000 +1000x-1200(\sqr{410000 +1000x})=50000-1000x 2000x+360000-1200(\sqr{410000 +1000x})=0 2000x+360000=1200(\sqr{410000 +1000x}) 20x+3600=12(\sqr{410000 +1000x})
removing sqrt:
400x^2+(3600)^2+144000x=144(410000 +1000x) with some math 400x^2+(3600)^2+144000x=144000x+59040000
400x^2=46080000
so x^2=115200
given that x = \sqrt{2} \times A
\sqrt{115200}= \sqrt{2} \times A \frac {\sqrt{115200}}{\sqrt{2}} = A \sqr{\frac {115200}{2}} =A \sqr{57600}=A
so A =240
First quadrant means both x and y are positive,
First condition:
√(〖(x+500)〗^2+y^2 )-√(〖(x-500)〗^2+y^2 )=600----(i)
Second condition:
x^2 + y^2 =〖400〗^2---(ii)
From (i)
√(x^2+1000x+〖500〗^2+y^2 )+√(x^2-1000x+〖500〗^2+y^2 )=600
√(〖400〗^2+1000x+〖500〗^2 )+√(〖400〗^2-1000x+〖500〗^2 )=600-----[from (ii)---> x^2+y^2=〖400〗^2]
Squaring both sides
2 (〖400〗^2+〖500〗^2 )-2 √(〖(〖400〗^2+〖500〗^2)〗^2-〖(1000*x)〗^2 )=〖600〗^2
2 (〖400〗^2+〖500〗^2 )-〖600〗^2 = 2 √(〖(〖400〗^2+〖500〗^2)〗^2-〖(1000*x)〗^2 )
√(〖(〖400〗^2+〖500〗^2)〗^2-〖(1000*x)〗^2 ) = 230000
(1000*x)〗^2=〖〖〖(400〗^2+〖500〗^2)〗^2-230000〗^2
x =339.411255
√2 A=339.411255
A = 240
The assertion that ( x , y ) is 6 0 0 units closer to ( 5 0 0 , 0 ) than to ( − 5 0 0 , 0 ) means that ( x , y ) is a point on the hyperbola 3 0 0 2 x 2 − 5 0 0 2 − 3 0 0 2 y 2 = 1 , subject to x > 0 . Note that 5 0 0 2 − 3 0 0 2 = 4 0 0 2 , so this equation can be simplified to 3 0 0 2 x 2 − 4 0 0 2 y 2 = 1 .
Additionally, since ( x , y ) is 4 0 0 units from the origin, it must be a point on the circle x 2 + y 2 = 4 0 0 2 . Therefore, 4 0 0 2 y 2 = 1 − 4 0 0 2 x 2 , so we can substitute this expression for 4 0 0 2 y 2 into the equation for the hyperbola and get 3 0 0 2 x 2 − 1 + 4 0 0 2 x 2 = 1 . Hence, x 2 ( 4 0 0 2 + 3 0 0 2 ) = 2 ( 4 0 0 2 ) ( 3 0 0 2 ) and x = 5 0 0 2 ⋅ 4 0 0 ⋅ 3 0 0 = 2 4 0 2 . Thus, the value of A we are looking for is 2 4 0 .
Problem Loading...
Note Loading...
Set Loading...
Solving x , y > 0 , x 2 + y 2 = 4 0 0 , ( x − 5 0 0 ) 2 + y 2 + 6 0 0 = ( x + 5 0 0 ) 2 + y 2 gives x = 2 4 0 2 , y = 8 0 7 . Thus, A = 2 4 0